Pendampingan Penguasaan Bahasa Inggris Siswa Sekolah Dasar Melalui Game-Based Learning (GBL) - Purwani, Wilujeng Asih; Dewi, Anita Rahmah; Rosyadah, Vina (TAAWUN, 2023)
In this modern era, English is an international language that must be mastered by all people. In the world of education, English is introduced from an early age through various methods. However, not all schools are able to apply effective learning methods according to the level and characteristics of students. As is the case in Dateng Village, Laren sub-district, the teaching and learning process in several elementary schools is still very ineffective, especially in learning English. Ineffectiveness has an impact on students’ motivation and enthusiasm for learning. One of the factors is the lack of fun learning methods. Therefore, the selection of media needs to be considered before learning activities. In this teaching and learning the Community Service team uses the Englsih for Young Learners theory approach with media suitable for elementary level students, namely through games to develop English vocabulary.. This media focuses on listening, listening, and speaking skills. The purpose of learning English is to increase students’ enthusiasm in learning English and improve English language skills that are more effective and fun. The results of community service are 1. Interest and ability of students in learning English is increased 2. Basic abilities, especially in English vocabulary are more varied